Design Curriculum Based on Outcome Based Education (OBE): Preparing Work Ready Graduates - Nesa Novrizal; Rio Ravi Muhammad; Rokimin (Universitas Darunnajah Jakarta, Indonesia, 2025)
This study explores how an Outcome-Based Education (OBE) curriculum design can help prepare graduates for the workforce. A qualitative approach is used to gain an in-depth understanding of how OBE principles are implemented in higher education and how they contribute to enhancing graduates' competencies in line with industry needs. Data for this study were obtained through a literature review and interviews with academics and education practitioners to identify key factors in developing an OBE-based curriculum. The findings indicate that OBE emphasizes the achievement of measurable learning outcomes that are relevant to the job market through the formulation of clear learning objectives, the use of teaching methods focused on skill development, and outcome-based assessments that evaluate graduates' readiness. By implementing an OBE-based curriculum, educational institutions can more effectively equip students with the skills and knowledge required by industry demands, thereby increasing their chances of securing jobs that align with their expertise.